2015
DOI: 10.1099/vir.0.000129
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the impact of Shimen and C strains of classical swine fever virus on Toll-like receptor expression

Abstract: Classical swine fever is one of the most important swine diseases worldwide and has tremendous socioeconomic impact. In this study, we focused on the signalling pathways of Toll-like receptors (TLRs) because of their roles in the detection and response to viral infections. To this end, two classical swine fever virus (CSFV) strains, namely the highly virulent CSFV Shimen strain and the avirulent C strain (a vaccine strain), were employed, and the expression of 19 immune effector genes was analysed by real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In addition, the increase of ROS impacts on the activation of NF-κB, MAPK ERK, JNK, p38, and PI3K-Akt signaling pathways (Thannickal and Fanburg, 2000 ; Kyaw et al, 2001 ; Qadri et al, 2004 ; Groeger et al, 2009 ; Yi et al, 2015 ; Zhang et al, 2016 ). However, CSFV fails to activate the NF-κB-signaling pathway (Chen et al, 2012 ; Cao et al, 2015 ). Thus, we speculated that CSFV may induce IL-8 production through ROS-mediated ERK, JNK, p38, or PI3K-Akt pathways, and the hypothesis will be further studied in future research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase of ROS impacts on the activation of NF-κB, MAPK ERK, JNK, p38, and PI3K-Akt signaling pathways (Thannickal and Fanburg, 2000 ; Kyaw et al, 2001 ; Qadri et al, 2004 ; Groeger et al, 2009 ; Yi et al, 2015 ; Zhang et al, 2016 ). However, CSFV fails to activate the NF-κB-signaling pathway (Chen et al, 2012 ; Cao et al, 2015 ). Thus, we speculated that CSFV may induce IL-8 production through ROS-mediated ERK, JNK, p38, or PI3K-Akt pathways, and the hypothesis will be further studied in future research.…”
Section: Discussionmentioning
confidence: 99%
“…TLR-7 binds with the ssRNA derived from CSFV and TLR-3 senses the replication intermediate dsRNAs ( Diebold et al, 2004 ; Sen and Sarkar, 2005 ; Chen et al, 2015 ). Intracellular detection of ssRNA by TLR-7 triggers the activation of transcription factors IRF-7 and NF-κB, which ultimately initiate the expression of type I IFNs including IFNα and IFNβ ( Lund et al, 2004 ; Cao et al, 2015 ). TLR-3 signaling activates the transcription factor IRF-3, which induces expression of the IFN-β and type III IFNs upon its entrance into the nucleus of cells ( Kawai and Akira, 2006 ; Chen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also revealed that CSFV Shimen infection of pMDMs leads to the activation of MAPK signalling pathways, while it fails to activate NF-κB. Furthermore, the Shimen infection reduces interferon regulatory factor (IRF)3 expression, but enhances IRF7 expression, thereby affecting the production of type I IFN responses 21 . HCV infection suppresses host innate immune response by degrading TRAF6 23 .…”
Section: Resultsmentioning
confidence: 92%
“…Viruses elicit the expression and release of a range of cytokines via the NF-κB-signalling pathway as part of the primary host defense mechanism. A previous study reported that CSFV failed to activate the NF-κB-signalling pathway 20 , 21 . Our findings showed that TRAF6 overexpression promoted NF-κB activation, and resulted in upregulation of IFN-β and IL-6 expression in PAMs.…”
Section: Discussionmentioning
confidence: 93%